Measuring dynamic effects of remittances on poverty and inequality with evidence from Kosovo - Arjola Arapi-Gjini; Judith Möllers; Thomas Herzfeld (Eastern European Economics, 2020)
This paper investigates dynamic effects of remittances on households' poverty and income distribution. Using state-of-the-art matching techniques, we measure impacts based on counterfactual scenarios, and make a step forward by applying for the first time a dose-response function approach to assess poverty effects due to variations in the time-length of receiving remittances. Our results suggest that remittances alleviate both absolute and relative poverty levels and lead to a marginal increase in inequality in the case of Kosovo. We further demonstrate that – although poverty reduction effects are stronger in the short-run – remittances have a positive poverty reduction effect over time. These findings have important welfare policy implications for low- and middle income economies with a high dependency on remittances.
Keywords: D10; D31; I32; J61; 330; poverty; inequality; migration; remittances; dose-response function; Kosovo